First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

An efficient digestion technique for the analysis of heavy metals, Ca and Al in solid waste incineration ash - Limo He; Eslam M. Hamed; Xuanhao Lin; Sam Fong Yau Li (Journal of Environmental Management, 2025)

Novel dopamine-derived carbon modified fe-based metal–organic framework enhanced aptasensor rendering ultrasensitive electrochemical detection of oxytetracycline - Jialing Song; Xiaoxuan Fan; Liang Ying Ee; Xuanhao Lin; Dengsong Zhang; Sam Fong Yau Li; Manhong Huang (Chemical Engineering Journal, 2024)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646

Dynamic Anthropometrics of Preschool Children in Taiwan for Playground Equipment Designs - I-Fang Cheng; Chien-Ju Lin; Li-Chieh Kuo; Bih-Jen Hsue; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Evidence-based Customized Ankle-Foot Orthosis with Energy Storage - Chih-Chun Lin; Chien-Hsien Yeh; Yi-Chun Tsai; Li-Chieh Kuo; Hsiu-Yun Hsu; Ping-Han Chuang; Kai Chang; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Anthropometric Database of the Preschool Children from 2 to 6 Years in Taiwan - I-Fang Cheng; Li-Chieh Kuo; Chien-Ju Lin; Hsiao-Feng Chieh; Fong-Chin Su (Journal of Medical and Biological Engineering, 2019)

Analysis of Electroencephalography Event-Related Desynchronisation and Synchronisation Induced by Lower-Limb Stepping Motor Imagery - Yi-Hung Liu; Li-Fong Lin; Chun-Wei Chou; Yun Chang; Yu-Tsung Hsiao; Wei-Chun Hsu (Journal of Medical and Biological Engineering, 2019)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Functional expression of the recombinant ATPase of orf virus - Fong-Yuan Lin; Kun-Wei Chan; Hsien-Chi Wang; Wei-Li Hsu; Min-Liang Wong (Archives of Virology, 2010)

p66Shc—a longevity redox protein in human prostate cancer progression and metastasis - Mythilypriya Rajendran; Paul Thomes; Li Zhang; Suresh Veeramani; Ming-Fong Lin (Cancer and Metastasis Reviews, 2010)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Ventral coloration differentiation and mitochondrial sequences of the Chinese Cobra (Naja atra) in Taiwan - Hua-Ching Lin; Shou-Hsien Li; Jonathan Fong; Si-Min Lin (Conservation Genetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Numerical comparison study of cloud microphysical parameterization schemes for a moderate snowfall event in North China - W. S. Lin; C.-H. Sui; C. Bueh; A. Wang; S. Fan; C. Wu; S. Fong; J. Li; J. Meng (Meteorology and Atmospheric Physics, 2007)